1996
DOI: 10.1055/s-2008-1052220
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Anosmia after Anterior Communicating Artery Aneurysms Surgery by the Pterional Approach

Abstract: Damage to the olfactory nerve during the pterional approach to the anterior communicating artery aneurysms has not previously been investigated in a quantified manner. In this retrospective study, 100 patients with anterior communicating artery aneurysms, for whom the pterional approach was employed, were observed from the point of view of postoperative olfactory nerve function. In the postoperative period only three cases suffered from the impaired sense of smell ipsilateral to the side of surgery. 15 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 3 publications
(8 reference statements)
0
37
1
1
Order By: Relevance
“…Plus, arachnoid dissection and mobilization of the olfactory nerve can release it from retraction. 1,3 The current study has several important limitations. First, it was based on a retrospective review of a small case series from a single institution.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Plus, arachnoid dissection and mobilization of the olfactory nerve can release it from retraction. 1,3 The current study has several important limitations. First, it was based on a retrospective review of a small case series from a single institution.…”
Section: Discussionmentioning
confidence: 92%
“…Based on results from previous studies of ruptured aneurysms, surgical clipping via a pterional approach and ACoA aneurysms are already known to present an increased risk to olfaction. 1,3,13,16 Aydin et al 1 revealed that 15% of patients with an ACoA aneurysm developed unilateral or bilateral olfactory dysfunction. Additionally, in a previous Sniffin' Sticks test, 14% of patients with a ruptured ACoA aneurysm had abnormal binostril olfaction after a pterional approach.…”
Section: Discussionmentioning
confidence: 99%
“…It must be point out that, the exact location of the Sylvian fissure medially is not always apparent and that the fissure does not always "open" in a clean arachnoidal plane, as is frequently illustrated [1][2][3][4][5][6][7][8][9][10][11]. It is possible to see the variations of the width of the Sylvian cistern and the middle cerebral artery position in some cases [1].…”
Section: Sylvian Dissectionmentioning
confidence: 99%
“…I got this Yasargil's approach named as "Yasargil Surgical Highway". Today, most neurosurgeons use one of these two basic surgical approaches, although with some minor modifications and refinements [1][2][3][4][5][6][7][8][9][10][11]. The pterional approach is commonly employed in surgery of the anterior circulation and upper basilar artery aneurysms, as well as for the tumors of orbital.…”
mentioning
confidence: 99%
See 1 more Smart Citation